Decentering Mañjuśrī: some aspects of Mañjuśrī’s cult in medieval Japan - Faure, Bernard (Studies in Chinese Religions, 2019)
Many scholars have studied Mañjuśrī’s role as bodhisattva of wisdom. However, while Buddhist deities have usually been studied ‘individually,’ I believe that they can only be understood in a broader context. A deity is not an individual, but the salient part of a network that includes, first of all, his acolytes, his entourage, but also his mount, his various manifestations, as well as a number of functionally similar deities. Indeed, all of the above can be seen as ‘emanations’ of an elusive, multifaceted and metamorphic fundamental power. To this end, the texts of the Japanese esoteric Buddhism give us precious indications of Mañjuśrī beyond the popular representation of the bodhisattva of wisdom: his fundamental ambivalence and his central importance in rites of subjugation.